Expansion energy of coal gas for the initiation of coal and gas outbursts. (1st January 2019) - An, Fenghua; Yuan, Yu; Chen, Xiangjun; Li, Zhiqiang; Li, Liyang
Highlights: New fractures by coal damage can affect gas expansion energy from coal obviously. Assuming desorption at atmospheric pressure in expansion energy calculation is viable. Gas conditions can affect the gas expansion energy for outburst significantly. Increase in coal seam depth could broaden the peak zone of gas expansion energy. Abstract: The study of coal and gas outburst mechanisms is necessary for the safety and efficiency in mining. Gas expansion energy is a major factor in outburst initiation. However, the amount of coal gas participating in outburst initiation is hard to estimate. In this study, considering the effect of coal damage and the environmental pressure change for desorption, a method to calculate gas expansion energy for outburst initiation is provided. Due to the reduction of the diffusion path, new fractures caused by coal damage can obviously affect gas expansion energy during outburst initiation. A peak zone of gas expansion energy during outburst initiation exists in front of the working face that belongs to the failure zone in coal mining and the zone of high gas pressure gradient. The peak zone is the risk source of the outburst and is the reason for the slabbing characteristic of the outburst. In outburst initiation, the variable pressure environment for gas desorption from the coal matrix has a limited effect on gas expansion energy for the outburst. Thus, the approximation of gas desorption with atmospheric pressure in the previous gas energy calculation is practicable. Gas conditions can affect the gas distribution in a coal mass and then obviously affect the gas expansion energy for an outburst initiation. Meanwhile, fracture development or the sorption time of the coal matrix has an obvious effect as well. It means tectonic coal could contribute much more gas expansion energy than primary-structure coal, causing high frequency and large power outbursts in tectonic regions. Unlike the effect on elastic energy accumulated in the coal mass, the increase of coal seam depth only broadens the peak zone of gas expansion energy and has little effect on the peak magnitude.